Introduction and motivation - Davis, Kristin E.; Babu, Suresh Chandra; Ragasa, Catherine (International Food Policy Research Institute, 2020)
Agricultural development is critical to the livelihoods of more than a billion small-scale farmers and other rural populations in developing countries. Challenges such as low productivity, persistent food insecurity and malnutrition, food price crises, natural resource depletion, changing and uncertain markets, environmental degradation, and climate change directly impact (and are impacted by) the agriculture sector and rural development. Agricultural extension and advisory services can help address these challenges by assisting farmers with advice and information, brokering and facilitating innovations and relationships, dealing with risks and disasters, and in many other ways.